Current employment status, occupational category, occupational hazard exposure and job stress in relation to telomere length: the Multiethnic Study of Atherosclerosis (MESA). Issue 8 (18th May 2013) - Fujishiro, Kaori; Diez-Roux, Ana V; Landsbergis, Paul A; Jenny, Nancy Swords; Seeman, Teresa
Abstract : Objective: Telomere length has been proposed as a biomarker of cell senescence, which is associated with a wide array of adverse health outcomes. While work is a major determinant of health, few studies have investigated the association of telomere length with various dimensions of occupation. Accelerated cellular aging could be a common pathway linking occupational exposure to several health outcomes. Methods: Leukocyte telomere length was assessed using quantitative PCR in a community-based sample of 981 individuals (age: 45–84 years). Questionnaires were used to collect information on current employment status, current or main occupation before retirement and job strain. The Occupational Resource Network (O*NET) database was linked to the questionnaire data to create five exposure measures: physical activity on the job, physical hazard exposure, interpersonal stressors, job control and job demands. Linear regression was used to estimate associations of occupational characteristics with telomere lengths after adjustment for age, sex, race, socioeconomic position and several behavioural risk factors. Results: There were no mean differences in telomere lengths across current employment status, occupational category, job strain categories or levels of most O*NET exposure measures. There was also no evidence that being in lower status occupational categories or being exposed to higher levels of adverse physical or psychosocial exposures accelerated the association between age and telomere shortening. Conclusions: Cellular aging as reflected by shorter telomeres does not appear to be an important pathway linking occupation to various health outcomes.